2019
DOI: 10.22190/fupes180607055r
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence of Procedures in the Development of Fine Motor Coordination Through Physical Activities and Movement Games in Preschool Children

Abstract: In order to successfully master the initial writing process that a child faces at school, it is necessary to develop fine motor coordination of the arm, hand and finger muscles. The aim of this paper is to provide the child with perceptual - motor activities, movement games as well as other physical activities that require precise movements and coordination between the two hands and arms and eyes to release the hand, hand and fingers, prepare the child for fine motor coordination and encourage initial writing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Motor skills are the ability to carry out a series of physical movements in business and coordination so that automatic movements are realized. The motor skills in question are skills in performing physical movements that require coordination between muscles and nerves to produce automated movements (Randjelović et al, 2019); (Uysal & Düger, 2020). Motoric ability is the quality of the results of individual movements in carrying out movements, both movements that are not sports or movements in sports, or the maturity of the appearance of motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…Motor skills are the ability to carry out a series of physical movements in business and coordination so that automatic movements are realized. The motor skills in question are skills in performing physical movements that require coordination between muscles and nerves to produce automated movements (Randjelović et al, 2019); (Uysal & Düger, 2020). Motoric ability is the quality of the results of individual movements in carrying out movements, both movements that are not sports or movements in sports, or the maturity of the appearance of motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…Any research, in which some kind of experimental treatment was conducted in preschool age, resulted in the improvement of all abilities that the researchers tried to influence (Iivonen, Nissinen, Sääkslahti, & Liukkonen, 2007;Hraski, Stojsavljević, & Hraski, 2009;Brown, 2010;Ohl et al, 2013;Daya, 2017;Uzunović et al, 2017;Randjelović et al, 2018). Even the increase in the total volume of physical exercise, with the same activities that are applied, gave positive effects on the improvement of fine motor skills of preschool children (Savičević, Suzović, & Dragić, 2012).…”
Section: Disscusionmentioning
confidence: 99%
“…On the other hand, in their longitudinal study, Uzunović et al (2017) with the help of BOT-2 battery tests obtained statistically significant differences between the group which conducted additional sports programs within preschool institutions, and the control group which had no additional activity, and thus found that the programmed sports school can affect the development of fine motor skills to a great extent. Randjelović, Stanišić, Dragić, Piršl, and Savić (2018) also spoke about the positive effects of physical activity and the order of the processes of developing physical coordination of preschool children, through different types of games. Through their research, they found that voluntary control and coordination between arm, hand and finger movements, both hands, as well as between hands and eyes, can be greatly improved with the help of guided and free physical activities on playgrounds, moving games and morning gymnastics.…”
Section: Introductionmentioning
confidence: 99%
“…El entrenamiento de esta coordinación se realiza a través de diversas actividades y ejercicios que contribuye al progreso de la motricidad fina de los infantes para mejorar su coordinación y así desarrollar el tono muscular, lateralización, control voluntario de los movimientos y coordinación de la mano, brazo, ojos y los dedos, favoreciendo la preparación de una escritura en el nivel inicial con proyección al siguiente nivel, teniendo en cuenta los periodos de avance acorde a la edad del niño (Randjelović et al, 2019). Sabiendo que, a mayor desarrollo de la coordinación viso manual se favorecerá la capacidad de manipulación y el agarre en trípode, incrementando positivamente su coordinación motora fina en los infantes y por ende en el proceso manual en el inicio de la caligrafía en preescolar (Alvis & Llerena, 2020).…”
Section: Coordinación Motora Finaunclassified